Feasibility of Preparation of Celery Hair Tonic (Apium Graviolens Linn) as A Hair Loss Treatment Cosmetic - Sari, Rahma; Minerva, Prima (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
Hair loss is experienced by many women today, hair loss health problems caused by one of the hereditary factors and hormones. Celery (Apium Graviolens Linn) is a plant that can be used as a fertilizer and accelerate hair growth. Many people today have returned to the new concept of “back to nature” by switching to natural materials because it is relatively safer. This study aims to determine the content of vitamin A and flavonoids, and determine the feasibility of celery extract seen from the smell, color, absorption, penelis preferences and pH test. This study is an experimental study with a quantitative description of the type of research. The research instruments are laboratory test, organoleptic test, physical properties test, hedonic test and pH test. Data collection using documentation and questionnaire methods. Descriptive analysis of the percentage data to explain the content contained in the celery Hair tonic and the feasibility of celery Hair tonic seen from the smell, color, absorption, penelis preferences and pH test. The results of Vitamin A contained in celery extract of 2,26gr/100 gr, and flavonoids of 18 mg/100 gr. Based on organoleptic tests, physical and hedonic properties showed that 86% smelled typical celery, 71% celery hair tonic dark brown, 57% celery hair tonic has sufficient absorption absorb, and 71% penelis said like celery hair tonic. PH test results showed celery Hair tonic is still in the pH balance of 4.53 pH. So celery can be used as the main ingredient in making hair tonic because celery plants include groups that contain flavonoid phytochemicals and vitamin A that can be used as alternative ingredients for hair health. It is expected that for the Department of Cosmetology and beauty FPP UNP research on the feasibility of celery Hair tonic preparations for hair loss health can be used as a reference in subsequent studies and can be refined.